Public Theology of Educational Engagement for Youth Development - Anthony, F.V. (University of jaffna, 2024)
Youth is a crucial category for the present and future of society. This is particularly true in the multifaceted Indian context. According to the National Statistical Office (NSO) of India, the youth population, defined as those between the ages of 15 and 29, comprised 27.2% of the country’s overall population of 1.3 billion in 2021. This proportion is expected to decline to 22.7% by 2036, but the youth population in numbers is projected to be still large, around 345 million. It means that the welfare of the Indian society is to a great extent determined by the wellbeing of youth who form about one-fourth of the population. If the Christian community with their educational institutions intend to contribute to the formation and development of multireligious Indian youth – particularly the emarginated and the poor - then Christians have to evolve a public theology of educational engagement. From the perspective of individual youth development, public theology must address the intellectual, emotional and behavioural wellbeing. The emerging question is how ecclesial faith can contribute to these varied aspects of youth development in dialogue with religious, cultural, psychological, social, political, economic, environmental studies. In this paper we wish to present some salient aspects of the empirical research undertaken among college students affiliated to Christian, Islamic and Hindu religious traditions in Tamil Nadu, India. The scope of the research was to scrutinize the human rights attitude of the young concerning right to life, civil rights, judicial rights, political rights, socioeconomic rights and environmental rights, and examining the role religions play with regard to it. Public theology of educational engagement would imply dealing with the impact of religions at meta-ethical, normative ethical and legal ethical levels and thus contribute to youth development.
Keywords: Youth development in India; Contribution of christian faith; Public theology of educational engagement